Reduction of brain dopamine concentration with dietary tyrosine plus phenylalanine depletion: an [11C]raclopride PET study. - Montgomery, A; McTavish, S; Cowen, P; Grasby, P (2003)
OBJECTIVE: Extracellular dopamine concentrations were estimated through measurement of [(11)C]raclopride binding with positron emission tomography after dietary manipulation of the dopamine precursors tyrosine and phenylalanine. METHOD: Healthy male subjects were scanned on two occasions: once after receiving a balanced amino acid drink and once after receiving a drink mixture from which tyrosine and phenylalanine were omitted. RESULTS: Dietary tyrosine and phenylalanine depletion increased [(11)C]raclopride binding in the striatum by a mean of 6%. The change in [(11)C]raclopride binding correlated significantly with the fall in the ratio of tyrosine and phenylalanine to large neutral amino acids. CONCLUSIONS: This is the first demonstration of an effect of a dietary manipulation on brain dopamine release in humans. This result provides support for the further investigation of the role of dietary manipulations in the treatment of neuropsychiatric disorders.